POSTPARTUM HEMORRHAGIC INCIDENCE BASED ON PARITIES IN PUBLIC HEALTH CENTER OF BOGOR CITY - Tri Diani Agustuti; Fitria Hari Wibawati; Utami Sulistyaningsih; Sara Tania; Elpinaria Girsang; Widia Astuti (Jurnal Keperawatan Respati Yogyakarta, 2022)
Acording to the data of World Health Organization (WHO), the number of maternal deaths in the world in 2017 was 216 per 100,000 live births or maternal deaths was about 303,000 death by the highest total occurred at developing country, that was 302,000 deaths. The number of maternal deaths in the developing country was 20 times higher than the maternal deaths at the developed country, that was 239 from 100.000 live births whereas in the developed country 12 per 100.000 live births in 2017. This research used survey method of descriptive quantitative analysis by retrospective approach. The sample of the research is gotten by total technic sampling. The data used in this research was univariate and bivariate analysis with Chi-Square statistical test. Based on the parity, it was found 18 (41.9%) respondents occurred grand multipara. Based on postpartum hemorrhagic, it was found 31 (72.1%) respondents occurred secondary hemorrhagic. From 43 respondents, it was found 16 (37.2%) respondents of grand multipara parity occurred postpartum hemorrhagic. Based on bivariate analysis result by Chi-Square analysis test was found the value of P-value 0,018 < 0,05 (alpha) so Ha is accepted. There is a correlation of parity with postpartum hemorrhagic at Bogor City, Indonesia. Keyword: Parity; Postpartum Hemorrhagic; Mother; Parities